Relationship between root and yield related morphological characters in pea (Pisum sativum L.) - Ciaglo-Androsiuk, Sylwia (Plant Breeding and Seed Science, 2012)
Relation between morphological traits of the root system and yield related traits is an important issue concerning efforts aiming at improving of ideotype of cultivated plants species, including pea. In this paper, to analyse the dependency between traits describing the root system morphology and yield potential, Person’s and Spearman's correlations as well as canonical correlations were used. Root system was analyzed in 14 and 21 day-old seedlings growing in blotting-paper cylinders. Yield po- tential of pea was analysed in a field experiment. Results of Person’s and Spearman's correlations revealed that number of lateral roots and lateral roots density were correlated witch yield related traits. Correlation between root length and shoot length was observed only for 14 day-old seedlings. The result of canonical correlations revealed that number of lateral roots and lateral roots density had the largest effect on yield re- lated traits. This work highlights, that in order to improve the yield of pea it might become necessary to under- stand genetic determination of morphological traits of the root system, especially number of lateral roots.